A evolução das atividades experimentais em livros didáticos de Química - Arthur, Thalita (Universidade Federal de São Carlos, 2011)
The objective of this study was to investigate the evolution of experimental activities presented in textbooks on chemistry from Brazil Empire until the present. The experiments are analyzed in books from the Library of Textbooks of College of Education at USP / SP, dating from 1875 to 2010. For the analysis of experiments, the books were divided into 6 (six) periods: 1875 to 1930, from 1931 to 1941, from 1942 to 1960, from 1961 to 1970, 1971-1996 (SCHNETZLER, 1978), from 1997 to 2010. With the exception of the first period, the criterion adopted was the time of utilization of the first Brazilian chemistry textbook; others refer to periods of validity of the major Brazilian educational reforms. When relating the experimental approach to the current legislation, there is consistency between the proposal and what fits in the books and also closely related to the historical moment. Through the analysis of the experiments we observed three different approaches: demonstrative, empiricist-inductivist and investigative. The experimental investigative activities are highlighted in the books of the last period.
The evolution of experimental activities in Chemistry texbook
Keywords: Química - estudo e ensino; Experimentação; Química - história; CIENCIAS EXATAS E DA TERRA::QUIMICA